Spin-dependent current in silicon p-n junction diodes - Tretyak, O.V.; Kozonushchenko, O.I.; Krivokhizha, K.V.; Revenko, A.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
We have used electrically detected spin-dependent paramagnetic resonance to
investigate the non-equilibrium conductivity in a silicon diode. In order to create
paramagnetic centers, we used diode with a polished surface (that includes p-n junction).
The dependence of relative changes in the amplitude of a signal under resonance
conditions and the total value of current through the diode were investigated. We have
found the presence of inversion channel on the surface of p-n junction and proposed the
model of the influence of spin resonance on the channel conductivity. The upper value of
the time constant inherent to the spin-dependent process was determined as
approximately 10⁻⁶ s . The influence of the spin-dependent process on the charge state in
inversion channel has been discussed.